A comparative assessment of indigenous vodka production from fermented nipa sap in Camarines Norte and Butuan City, Philippines - Rasco, Eufemio T. Jr (Asia Life Sciences : the Asian International Journal of Life Sciences, 2010)
Nipa (nypa fruticans Wurmb), a mangrove palm found in many coastal areas of the Philippines, is known to be 3-4 times more productive than sugar cane in producing alcohol. However, the level of its current utilisation for this purpose is very low and confined to a few isolated places. The main product using a highly variable traditional technology is "nipa vodka", a clear alcoholic drink with 30-40% alcohol. Nina vodka is obtained from distillation of fermented sap collected from the cut stalk of semi-mature fruit heads. The paper describes and comparatively analyses the traditional practices used by nipa vodka producers in Vinzons, Camarines Norte and Butuan City. The main differences between the techniques used in the locations studied are: (a) sap collection in Butuan City uses close bamboo tubes that are less exposed to the environment; in Vinzons, bamboo tubes are open at the top; (b) the distillation set-up in Vinzons uses a condenser that is cooled by a continuously flowing water; in Butuan City, the condenser is cooled by water that is replaced in batches as it warms; (c) heat loss is better controlled in Butuan City because of the use of a wooden distilling column and an enclosed furnance. Recommendations are offered to improve the quality of the toddy, reduce vapor and heat losses during distillation, improve the recovery of alcohol and develop a set of good manufacturing practices for vodka production.